2017
DOI: 10.1101/152488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of recollection by slow gamma dominating mid-frequency gamma in hippocampus CA1

Abstract: Behavior is used to assess memory and cognitive deficits in animals like Fmrl-null mice that model Fragile X Syndrome, but behavior is a proxy for unknown neural events that define cognitive variables like recollection. We identified an electrophysiological signature of recollection in mouse dorsal CA1 hippocampus. During a shocked-place avoidance task, slow gamma (SG: 30-50 Hz) dominates mid-frequency gamma (MG: 70-90 Hz) oscillations 2-3 seconds before successful avoidance, but not failures. Wild-type but no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 83 publications
(11 reference statements)
8
55
1
Order By: Relevance
“…The task requires intact hippocampal activity 7,8 , and persistent PKMzeta (PKMζ)-mediated long-term potentiation (LTP) of hippocampal synaptic function [9][10][11] . Hippocampus place cell discharge during the task mirrors ongoing performance as well as cognitive control of switching between task relevant and irrelevant information, demonstrating representational multi-tasking [12][13][14] . Furthermore, resembling effective CBT, preemptive training is sufficient to prevent subsequent neuropsychiatric-related cognitive impairments in a neurodevelopmental rat model 15 .…”
Section: Discussionmentioning
confidence: 90%
“…The task requires intact hippocampal activity 7,8 , and persistent PKMzeta (PKMζ)-mediated long-term potentiation (LTP) of hippocampal synaptic function [9][10][11] . Hippocampus place cell discharge during the task mirrors ongoing performance as well as cognitive control of switching between task relevant and irrelevant information, demonstrating representational multi-tasking [12][13][14] . Furthermore, resembling effective CBT, preemptive training is sufficient to prevent subsequent neuropsychiatric-related cognitive impairments in a neurodevelopmental rat model 15 .…”
Section: Discussionmentioning
confidence: 90%
“…We examined several published datasets of extracellular recordings in hippocampal areas CA1 and CA3 during open field exploratory foraging. The following datasets were included in the analysis: two CA1 sessions from a teleportation experiment reported in Jezek, Henriksen, Treves, Moser, and Moser (), five CA1 sessions recorded in the Buzsaki lab (Mizuseki et al, 2013; Mizuseki et al, ; Mizuseki, Sirota, Pastalkova, & Buzsaki, ) (specifically session ec14.215, ec14.277, ec14.333, ec14.260, and ec15.047 from the openly available hc‐3 dataset), 16 CA1 sessions from wild‐type mice, and 16 CA1 sessions from Fmr1‐null mice recorded from Sparks, Talbot, Dvorak, and Fenton (), Talbot et al (), and Dvorak, Radwan, Sparks, Talbot, and Fenton (), also taken from the openly available hc‐16 dataset, 28 CA1 sessions in three rats from a remapping experiment reported in Schlesiger et al () and Schlesiger et al () and, finally, 178 CA3 sessions from seven rats in 11 rooms reported in Alme et al (). Details about the recordings and the experimental settings can be found in the respective references.…”
Section: Resultsmentioning
confidence: 99%
“…Besides theta rhythms and SWRs, gamma rhythms have also been hypothesized to play a role in learning and memory [22][23][24][25][26][27][28][29][30] . Previous studies have also suggested that "slow" (~25-55 Hz) and "fast" (~60-100 Hz) gamma rhythms are associated with different inputs to the hippocampus [31][32][33][34] .…”
Section: Errors Were Not Associated With Deficits In Gamma Phase Modumentioning
confidence: 99%
“…A number of rodent studies have also related gamma rhythms to performance on mnemonic tasks [22][23][24][25][26][27][28][29][30] . In addition, recent studies have shown that low (~25-55 Hz) and high (~60-100 Hz) frequencies of hippocampal gamma activity are associated with CA3 and entorhinal cortex inputs to subfield CA1 [31][32][33][34] , respectively, raising the possibility that "slow" and "fast" gamma subtypes facilitate transmission of different inputs to CA1 place cells.…”
Section: Introductionmentioning
confidence: 99%